Vegetarian diet - how does it affect our body? - Tekiela, Natalia; Papachristoforu, Natalie; Michałka, Daria; Gałuszka, Zuzanna; Makar, Monika; Bartuś, Tomasz; Bąk, Emilia; Głowacka, Justyna; Aleksandra Kocjan,; Chmiel, Radosław (Quality in Sport, 2025)
Introduction and Purpose of Research: Vegetarianism, characterized by the exclusion of meat, poultry, fish, seafood, and their derivatives, has gained popularity as studies continue to highlight its positive impact on health. This study aims to comprehensively evaluate the health and lifestyle impacts of vegetarian diets by examining both the benefits and potential risks. Review Methods: The review is grounded in findings from 40 recent studies sourced through a systematic search of open-access databases, including PubMed and Google Scholar, focusing on literature published between 2000 and 2024. Abbreviated description of the state of knowledge: Vegetarian diets are associated with significant health benefits, including reduced risks of chronic diseases such as heart disease, type 2 diabetes, and obesity, largely due to their high content of fiber, antioxidants, and healthy fats. Additionally, vegetarians tend to have lower BMI and improved cholesterol and blood pressure levels. However, unbalanced vegetarian diets may lead to deficiencies in essential nutrients such as protein, vitamin B12, iron, zinc, and omega-3 fatty acids, which can impact overall health. Conclusion: Properly planned vegetarian diets are healthy, nutritionally correct and can be beneficial in the prevention and treatment of certain diseases. Careful selection of meal ingredients and adequate supplementation are key to maximising the benefits and counteracting the potential risks associated with such diets.